+0  
 
0
245
2
avatar

$${{\mathtt{7}}}^{{\mathtt{x}}}{\mathtt{\,\small\textbf+\,}}{{\mathtt{7}}}^{\left({\mathtt{x}}{\mathtt{\,-\,}}{\mathtt{2}}\right)}{\mathtt{\,\small\textbf+\,}}{\mathtt{7}}{\mathtt{\,\times\,}}\left({\mathtt{x}}{\mathtt{\,\small\textbf+\,}}{\mathtt{1}}\right) = {\mathtt{7}}{\mathtt{\,\times\,}}{\mathtt{393}}$$

Guest Aug 18, 2015

Best Answer 

 #1
avatar+17728 
+5

If the original problem were entered slightly incorrectly:

  7x + 7(x - 2) + 7(x + 1)  =  7·393

7x + 7· 7-2 + 7x · 71  =  7·393

(1 + 7-2 + 7) · 7x  =  7·393

(1 + 1/49 + 7) · 7x  =  7·393

(393/49) · 7x  =  7·393

 7x  = (7·393)·(49/393)

 7x  = 7·49 = 73

x = 3

geno3141  Aug 18, 2015
Sort: 

2+0 Answers

 #1
avatar+17728 
+5
Best Answer

If the original problem were entered slightly incorrectly:

  7x + 7(x - 2) + 7(x + 1)  =  7·393

7x + 7· 7-2 + 7x · 71  =  7·393

(1 + 7-2 + 7) · 7x  =  7·393

(1 + 1/49 + 7) · 7x  =  7·393

(393/49) · 7x  =  7·393

 7x  = (7·393)·(49/393)

 7x  = 7·49 = 73

x = 3

geno3141  Aug 18, 2015
 #2
avatar
0

$${{\mathtt{7}}}^{{\mathtt{x}}}{\mathtt{\,\small\textbf+\,}}{{\mathtt{7}}}^{\left({\mathtt{x}}{\mathtt{\,-\,}}{\mathtt{2}}\right)}{\mathtt{\,\small\textbf+\,}}{\mathtt{7}}{\mathtt{\,\times\,}}\left({\mathtt{x}}{\mathtt{\,\small\textbf+\,}}{\mathtt{1}}\right) = {\mathtt{7}}{\mathtt{\,\times\,}}{\mathtt{393}} \Rightarrow {\mathtt{x}} = {\mathtt{\,-\,}}{\frac{\left({\mathtt{50}}{\mathtt{\,\times\,}}{{\mathtt{7}}}^{\left({\mathtt{x}}{\mathtt{\,-\,}}{\mathtt{2}}\right)}{\mathtt{\,-\,}}{\mathtt{2\,744}}\right)}{{\mathtt{7}}}}$$

Easy one and difficulty:normal 

Guest Aug 19, 2015

27 Online Users

avatar
avatar
avatar
New Privacy Policy (May 2018)
We use cookies to personalise content and ads, to provide social media features and to analyse our traffic. We also share information about your use of our site with our social media, advertising and analytics partners.  Privacy Policy